Can credit ratings create value for the Icelandic financial market? - Sveinn Héðinsson 1986- (2015)
Credit ratings are considered an important part of today’s financial markets and contribute to increased investor protection, market efficiency and transparency in the market. While ratings have come under criticism for the role they played in the financial crisis in 2008, their presence in modern financial markets is still considered important. Ratings have a short history in Iceland and their use is not highly established among market participants. This thesis examines whether any potential value could be created in the Icelandic financial market with increased usage of credit ratings. It, furthermore, analyzes whether international credit rating methodologies are valid when rating an Icelandic organization and how the financial crisis in 2008 affected the credit rating market and its subsequent effect on ratings in Iceland. The analysis was done by reviewing credit rating agencies, their role and assigned credit ratings they use. This involved examining prior research and conducting interviews with domestic market participants. The main results indicate that with increased usage, ratings could increase comparability between potential investments and improve investors risk assessments and risk management. Moreover, ratings could potentially reduce the overall risk of the market and lower aggregated costs for market participants. Additional conclusions are that it is important to use similar rating methodologies as the larger international agencies to maintain comparability. The financial crisis also initiated a string of regulatory changes surrounding ratings that are likely to be introduced in the Icelandic market in the foreseeable future. Lastly, the way forward for credit ratings in Iceland is considered, by identifying steps that could assist with the proper establishment of ratings in the Icelandic financial market. Keywords: Credit ratings, asymmetric information, market efficiency, credit risk, Icelandic financial market.